International Public Sector Accounting Standard Implementation and Performance of Public Sector in Nigeria - Joy Nwanyisunday Konze (IIARD International Journal of Banking and Finance Research, 2026)
The study focused on international public sector accounting standard implementation and performance of public sector in Nigeria. Survey research design was adopted. The data were collected through questionnaire administration. The population of the study is made up of 100 management and staff of Abia state Ministry of Finance while the sample size of 80 staff was derived using convenience sampling. The data collected were analyzed using ordinary least simple regression analysis. The result revealed that Public Sector Accounting Standards implementation has a significant effect on the accountability of public sector in Nigeria. The result also revealed that Public Sector Accounting Standards implementation has a significant effect on the efficiency of public sector in Nigeria. The result further revealed that Public Sector Accounting Standards implementation has a significant effect on the effectiveness of public sector in Nigeria. Based on the findings, the study concludes that international public sector accounting standards affect the performance of public sector in Nigeria. Therefore, the study recommends that If Nigerian government is actually sincere and serious about tackling corruption in the country and stop cases of financial mismanagement, teaming and ladling; and prepare financial statements that could make full disclosure of every material fact and figure, full implementation and sustenance of IPSASs in the public sector is indispensable. The study also, recommend that training and development programs should be organized to equip staff and management of the various public sector institutions to enable them to apply IPSAS properly for optimum result that would enhance efficiency in public sector.